1998
DOI: 10.1021/jp9728621
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Hydrogen-Bonding Arrangement in Solid Triphenylmethanol:  An Investigation by Solid-State 2H NMR Spectroscopy

Abstract: Dynamic properties of the hydrogen-bonding arrangement in a selectively deuterated sample of solid triphenylmethanol (Ph3COD) have been studied by wide-line 2H NMR spectroscopy. In the crystal structure of Ph3COD, the molecules form hydrogen-bonded tetramers, with the oxygen atoms positioned approximately at the corners of a tetrahedron. The tetramer has point symmetry C 3 (rather than T d ); three of the Ph3COD molecules (denoted as “basal”) are related to each other by a 3-fold rotation axis, and the fourth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 15 publications
1
47
0
Order By: Relevance
“…Thus, the timescales for the hydrogen bond dynamics and the phenyl ring dynamics differ by at least five orders of magnitude, and it is clear that the dynamics of the hydrogen bonding arrangement and the dynamics of the phenyl rings are not correlated to one another. We note that the 1801-jump motion of each phenyl ring interconverts two orientations that are indistinguishable by diffraction techniques, and thus the structures determined from single-crystal X-ray diffraction [1] and single-crystal neutron diffraction [2] provide no hint for disorder with respect to the orientations of the phenyl rings (unlike the situation for the disorder in the hydrogen bonding arrangement, which is suggested from the single-crystal X-ray diffraction data and proven by the single-crystal neutron diffraction data). Finally, we note that the 2 H NMR technique probes the dynamic properties of individual deuterons, and does not provide any insights on whether the 1801 jumps of the three phenyl rings in a given molecule occur in a concerted fashion or whether they are independent of one another.…”
Section: Article In Pressmentioning
confidence: 71%
See 2 more Smart Citations
“…Thus, the timescales for the hydrogen bond dynamics and the phenyl ring dynamics differ by at least five orders of magnitude, and it is clear that the dynamics of the hydrogen bonding arrangement and the dynamics of the phenyl rings are not correlated to one another. We note that the 1801-jump motion of each phenyl ring interconverts two orientations that are indistinguishable by diffraction techniques, and thus the structures determined from single-crystal X-ray diffraction [1] and single-crystal neutron diffraction [2] provide no hint for disorder with respect to the orientations of the phenyl rings (unlike the situation for the disorder in the hydrogen bonding arrangement, which is suggested from the single-crystal X-ray diffraction data and proven by the single-crystal neutron diffraction data). Finally, we note that the 2 H NMR technique probes the dynamic properties of individual deuterons, and does not provide any insights on whether the 1801 jumps of the three phenyl rings in a given molecule occur in a concerted fashion or whether they are independent of one another.…”
Section: Article In Pressmentioning
confidence: 71%
“…2.9 Å ) within the tetramer are consistent with the tetramer being held together by O-H?O hydrogen bonds. Although the hydrogen atoms of the hydroxyl groups were not located in the structure determination from single-crystal X-ray diffraction data (suggestive of possible disorder of the hydrogen bonding arrangement), subsequent single-crystal neutron diffraction studies [2] confirmed that the hydrogen bonding arrangement in this material is indeed disordered (each hydroxyl hydrogen atom is disordered between different sites with fractional occupancies, each corresponding to the formation of an O-H?O hydrogen bond along a different O?O edge of the O 4 pyramid).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…As there are six O⋅⋅⋅O edges of the tetramer but only four O−H⋅⋅⋅O hydrogen bonds, there are several different permutations for arranging the O−H⋅⋅⋅O hydrogen bonds, and disorder of the hydrogen‐bonding arrangement may be anticipated, consistent with the fact that hydrogen‐atom positions were not reported for the hydroxyl groups in the crystal structure determined from single‐crystal X‐ray diffraction data at ambient temperature. To explore whether the disorder of the hydrogen‐bonding arrangement is dynamic, solid‐state 2 H NMR studies were carried out on the selectively deuterated material Ph 3 COD.…”
Section: Dynamic Properties Of Crystalline Solidsmentioning
confidence: 99%
“…A large number of studies have been performed using 2 H as the probe of molecular properties; examples are dynamics of silanol groups in silica gels and nanoparticles [3,4], methylene group dynamics [5], conformations of membrane lipids [6], dynamics of different segments of polymer chains [7], distinguishing among and characterizing polymorphs [8] and hydrogen-bond arrangements in various materials [9,10]. Typically, such studies concerned 2 H populations at respective single sites in which case the whole spectrum reported on the same phenomenon.…”
Section: Introductionmentioning
confidence: 99%